Closed rupture of a flexor profundus tendon to the little finger caused by asymptomatic pisotriquetral osteoarthritis: A case required differentiation from the tendon rupture due to hamate bony irregularity by bone erosion. (June 2022) - Hatori, Yuhei; Tajika, Tsuyoshi; Kuboi, Takuro; Saida, Ryuta; Chikuda, Hirotaka
Carpal joint osteoarthritis and the formation of bony irregularities of the carpal bone cause closed flexor tendon ruptures. This report describes a case of a flexor profundus tendon closed rupture of the little finger due to asymptomatic pisotriquetral osteoarthritis in a 73-year-old woman, which required differentiation from tendon rupture due to hamate bony irregularity due to bone erosion. Computed tomography showed cortical bone irregularities of the hamate and the narrowing of the pisotriquetral joint space, and a bony spur on the radial side of the pisiform. Intraoperative findings revealed the capsule of the pisotriquetral joint was torn on the radial side. Pisiform-hamate ligament disruption and the bony spur on the pisiform were found on this side. However, the flexor tendon floor on the hamate was intact. Surgical resection of the pisiform and a free tendon interposition graft for tendon rupture restored the good function of the little finger. Particular attention should be paid in making the diagnosis in cases with multiple possible triggers for closed flexor tendon rupture.